Cyberspace as a new sphere of the state of exception - Karahan, Süleyman Alper (İstanbul Bilgi Üniversitesi, 2020)
ABSTRACT: The primary purpose of this study is to understand the relationship between cyberspace, law, and the sovereign through the concept of the exception of Agamben and Schmitt. In this respect, the central assertion of this study is that a new sphere of exception with an uncertain future is being formed over cyberspace today. To confirm this assertion, the reasons for which this claim was made will be discussed briefly during the introduction, and some academic papers will be examined, which were written during the period that cyberspace came into existence. Afterward, via the current statistics and countries that use strict censorship towards cyberspace such as Turkey and Iran, the efforts of sovereign powers to control cyberspace will be examined, and, once again, through the concept of exception, the ambivalent relationship between the sovereign and cyberspace will be analyzed. In the following chapters, the effects of new communication technologies on social and governmental practices and the spatiality of cyberspace will be discussed using the work of McLuhan. Finally, this argument will be supported by both historical and contemporary examples and as a result, a different kind of perceptive will be offered for this exceptional sphere and its participants.

ÖZET: Bu çalışmanın amacı siberuzayın hukuk ve egemenle olan ilişkisini Agamben ve Schimitt’in istisna kavramı üzerinden anlamaya çalışmaktır. Bu doğrultuda çalışmanın esas iddiası günümüzde siberuzay üzerinden akıbeti belli olmayan yeni bir istisna alanının şekillendiği yönündedir. Bu iddiayı doğrulayabilmek adına, öncelikle giriş bölümünde bu iddianın hangi sebeplerle ortaya atıldığına kısaca değinilip, ardından siberuzayın ilk ortaya çıktığı yıllarda konuyla ilgili yapılan kimi çalışmalar ele alınacak. Sonrasında güncel istatistiki analizler ve siberuzaya karşı yoğun sansür uygulayan Türkiye, İran ve benzer durumda ülkeler üzerinden egemen güçlerin siberuzayı kontrol çabaları tartışılıp bu durumun istisna kavramı ile olan ilişkisi irdelencek, sonrasında yine istisna kavramı üzerinden egemen ve siberuzay arasındaki ikircikli ilişki ele alınacaktır. Ardından McLuhan’ın çalışmaları üzerinden tarih boyunca yeni iletişim teknolojilerinin toplumsal ve yönetimsel pratikler üzerindeki etkileri incelenip yine McLuhan üzerinden siberuzayın özgün mekansallığı tartışılacak. Nihayetinde de bu argüman hem tarihsel hem de güncel örneklerle desteklenip bu yeni istisnai alanın kendisine ve katılımcılarına dair farklı bir perspektif sunulmaya çalışılacaktır.
İstisna haline yeni bir alan olarak siber uzay
Keywords: siber uzay; istisna hali; internet sansürü; Giorgio Agamben; Marshall McLuhan; cyberspace; the state of exception; internet censorship